Community development in Asia and the Pacific - Pawar, Manohar S. (Routledge studies in development and society ;, 2009)
This book familiarizes readers with the Asia-Pacific region, presents the major social, economic and political issues, maps contemporary community development trends, and critically analyses the challenges of and opportunities for community development practice in the Asia-Pacific region.